Development of Filtration System using Chitosan and Silica Sand as Adsorbents for Reducing Salinity of Water for Micro-Irrigation : Developing filtration system for reducing salinity of water for micro-irrigation - Amarpreet Singh; Sunil Garg; Mukesh Siag; Jain, Ritesh (Journal of Soil Salinity and Water Quality, 2023)
A study was conducted to develop filtration technique by using chitosan and silica sand as adsorbents for reducing salinity of water for irrigation purpose. Chitosan is biopolymer which is extracted by alkaline deacetylation (40–50% NaOH) of chitin. It is an abundant natural biopolymer obtained from the exoskeletons of crustaceans and arthropods which is a non-toxic copolymer consisting of b-(1,4)-2-acetamido-2-deoxy-Dglucose and b-(1,4)-2-anaino-2-deoxy-D-glucose units. The chitin is produced after crushed, washed and demineralized with 1N HCL from shrimp shell. It is widely used in agricultural fields, medicinal and removal of inorganic contaminants (e.g trace metals) from wastewater and soil. Silica sand is also known as quartz sand and is produced from quartz stone by crushing. It is mainly the compound of silicon and oxygen and is used for adsorption purposes and glass making factories. Nanoporous silica materials have great applications in catalysis, separation and wastewater treatment because of their large surface areas, narrow pore size distribution and high adsorption capacities. The adsorbent chitosan and silica sand was able to reduce electrical conductivity (EC) by approx. 24 % and 12 % respectively. Optimum contact time for both adsorbents was found out to be 30 minutes.